Recognizing myself in my Expressive Body: A Phenomenological Account - Forlè, Francesca (Itinerari, 2023)
In this paper I would like to investigate the possibility of one’s recognition of oneself in his/her lived body. Specifically, I will maintain the thesis that one can recognize him/herself as a person in his/her bodily expressive behaviour. In order to do so, I will give an account of the latter that, even recognizing the pre-reflective nature of bodily expressions, tries to highlight their belonging to the personal sphere of our life as embodied beings. At the basis of such an account, the idea of an individual bodily expressive style as a counterpart of one’s whole personal style will be developed.